Development of a Semantic Expert System for Analyzing the Performance of Devices and Communication Systems - Dolin, G. A. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
There is a need to universalize the diagnostic processes of the operability of various radio technical devices and communication systems (RDCS). However, the presence of a wide range of ISSS requires different, sometimes extremely specific, approaches to their diagnosis. In addition, there is no universal method for storing and processing information containing signs of certain malfunctions, deviations in the quality indicators of the RDCS operation, the reasons for their occurrence and how to eliminate them. It is proposed to solve this problem by using an automated analysis of the quality indicators of the work of the ISSS in the semantic expert system. It will allow you to flexibly associate any indicator of the quality of the RDCS with the cause that influenced it, as well as to link the latter with the method or methods of eliminating the cause, which will provide the proposed algorithmic and software with the opportunity to accumulate knowledge in the field of performance analysis and act as an expert in the process of diagnosing the RDCS.